TREBUCHET: as body practice, research and performance - Triarou, Avgoustina (My University, 2025)
This written component of my Master’s thesis is a tribute to Trebuchet as a body practice, an artistic research and a performance. I use writing as its reflective and exploratory companion and I engage in a process of articulating and understanding the methodology that emerged during the artistic part of my thesis. Rather than separating theory and practice, this thesis weaves them together, mirroring the integrated approach that shaped the development of Trebuchet. Central to the work is the formation of a body practice, an evolving methodology rooted in sensorial, experiential, and somatic research, which aims to center the intelligence of the moving body as both the origin and site of inquiry. Drawing on concepts such as enactive perception (Alva Noë), reversibility theory (Maurice Merleau-Ponty), haptic visuality (Laura U. Marks), affect theory (Brian Massumi), and philosophical writings by Diego Agulló, I investigate how movement propositions of Trebuchet body practice become tools for reflection, transformation, and creation and how theory, and body knowledge can intertwine and inform one another. The thesis is structured in three chapters: the first focuses on the approach of the body practice as a way of working, reflecting on the dynamic role of the choreographer as facilitator and emphasizing the idea of problem projection as a generator for movement and choreography; the second explores the content of the practice through two central movement propositions- ‘Push and Sink In’ and ‘Charge and Throw’- tracing their development, tools, and conceptual and somatic influences; and the third examines how the body practice translates into performance, composition, and audience experience. Through this writing, I attempt not only to document, but to stay in conversation with the process, allowing the methodology to continue shifting and revealing itself through language.
Keywords: fi=koreografia|sv=koreografi|en=Choreography|